Allah Berharap pada Manusia: Teologi dengan Paradigma ‘Kebebasan’ - Sunarko, Adrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2016)
The author introduces a way of theologising by way of a particular paradigm, that is, ‘freedom’ paradigm. From the philosophical viewpoint this way of thinking according to the paradigm is chosen with the consideration that it has become one of the central themes in modern thought, is not under the level of reflection reached by the modern thought, and conforms the requirement of reason to borderlessly question the fundamental cause of everything. From the theological viewpoint, the choice for this paradigm has a consequence that ‘freedom’ becomes the reference, towards which theological reflection always directs itself. The author shows that ‘freedom’ paradigm brings the potential to be the reference in understanding and formulating Christian fundamental doctrines on many themes: on God and the reality of creation, humanity (theological anthropology), Jesus Christ (Christology), grace and sacraments, concepts of salvation (soteriology), history and its final meaning (eschatology), actual themes like human rights, freedom to have religion, et cetera.